Gastro-intestinal helminths of ducks: Some Epidemiologic and pathologic aspects (Journal of the Bangladesh Agricultural University, 2010)
A total of 206 ducks were subjected to routine postmortem examinations from July 2007 to June 2008. Of the ducks examined, 167 (81.1 %) were infected by one/more species of gastro-intestinal helminths. A total of ten species of helminth parasites were recovered from gastrointestinal tract, of which four species were trematodes namely: Echinostoma revolutum, Notocotylus attenuatus, Hypoderaeum conoideum and Echinoparyphium recurvatum; two were nematodes, namely, Amidostomum anseris, Capillaria contorta; two were cestodes, viz, Hymenolepis coronula and Fimbriaria fasciolaris and two species belonged to acanthocephala such as, Arythmorhynchus anser and Filicollis anatis. Single double and mixed infections were found in 78 (46.7%), 46 (27.5%) and 43 (25.8%) ducks, respectively. Prevalence of gastrointestinal helminth was significantly (P 1 year of age (31.1%). Helminth infection was significantly (P